Analysis of chemical and biochemical composition of fertile and sterile hydatid cyst fluids of human origin: Haider Barakat Abbas and Athmar K. Abbas. ALazawi - Abbas, Haider Barakat (The Iraqi Journal of Veterinary Medicine, 2017)
The present study were made for analysis of major chemical and biochemical components of twenty hydatid cysts fluids include two group (10 fertile cysts and 10 sterile cysts) obtained from the lung and liver of 29 infected patients admitted to medicine city hospital for operation during a period of 6 month these components were measured by colorimetric assay kits (Biolabo®, Human). Results revealed marked (P<0.05).differences in the mean values, particularly among enzymes (Glutanicoxaloacetic transaminase, Glutanic pyruvic transaminase and Alkaline phosphatase), between fertile and sterile fluids while Lactate dehydrogenase level was exhibited high activities in fertile and sterile isolates, these values was less than normal values in serum . The mean values of Iron, Zinc Sodium Phosphorus and potassium, were found higher in fertile isolates, while marked decrease in sterile isolates. Furthermore, the Copper revealed quantitative differences (P<0.05) between the two isolates. Manganese and chloride constituted the major volume in the fluid anions, in fertile and reach maximum in sterile fluid. Differences were detected in the levels of glucose of fertile which increased significantly (P<0.05). The data detected no significant difference (P>0.05) in total protein which exhibit high in fertile and sterile fluid. Also Calcium and Magnesium mean values revealed same in both isolates. Trace elements like Urea, Uric acid, Bilirubin Creatinine and Lipid increase in liver diseases such as (Cholesterol, and Triglycerides) level was found higher in fertile and sterile isolates. In compare with previous studies the present investigations reflected quantitative difference in mean values of biochemical parameters of fertile and sterile of hydatid cyst fluids contributed to fertility of cyst and viability of protoscoles. Fertile cyst which contain broad capsule and protoscoles which responsible of high concentration in these elements than sterile fluid which lack the broad capsule and protoscoles , which may pointed some variable in parasite metabolism endurance, growth rate, intermediate host specificity location of cyst among lungs or livers or even strain variation.